Tingkat Kepraktisan Penggunaan E-learning pada Model Pembelajaran Blended Learning di Tingkat SMA - Monica Fransisca; Yuliawati Yunus (Jurnal KomtekInfo, 2021)
Technological developments have a considerable influence on education, especially in learning media. Learning media is no longer conventional but is starting adapted with existing technology. The results of the initial observations found that the majority of senior high schools already have facilities for technology-based learning media, but the utilization of technology-based learning media is still very low. This resulted in less utilization of school facilities which already provided. Based on these observations and references from existing researches, it is assumed that e-learning, which is one of the technology-based learning media, can be used as a learning media for blended learning models. This research purpose was to produce an e-learning as learning media and the assessment level of practicality. This research used the Research and Development’s method with four-D development procedures to examine the level of practicality. To assess the level of practicality of e-learning, an assessment through a questionnaire was given to randomly selected subjects. The practicality assessment questionnaire consists of three main indicators such as indicators state of use, effectiveness of learning time and indicators of benefits. Referring to the results of the assessment, the average level of e-learning’s practicality is 80.70% so it can be concluded that e-learning is practical to be used as a learning media.